Applied electronic material based on ionogel from recycled plastics - Guo, Ziyan (Nanyang Technological University, 2021)
This thesis describes the fabrication of functional electronic materials such as ionogels from recycled plastics, via a facile, one-pot process. Oligomers easily obtained from polyethylene terephthalate degradation can be formed into an ionogel that can be potentially utilized as an electronic material in fields such as batteries, actuators, sensors. Ionic liquids and cleaving agents rapidly degrade polyethylene terephthalate into oligomeric gel-like materials. Different cleaving agents and ionic liquids are utilized to demonstrate the suitability of this mechanism for preparing ionogels. This universal process can be applied on polyethylene terephthalate and various waste plastic, including several types of condensation polymers whose chemical linkages are susceptible to hydrolysis or glycolysis. Glycerol was proven to be the cleaving agent that can obtain the ionogel with highest conductivity. Hence, the ionic conductivity of ionogels was optimized and studied using different reaction conditions. The as-prepared ionogels from waste polyethylene terephthalate should possess good ionic conductivity and desirable attributes for various applications, including solid electrolytes and dielectric actuators.